The Critical Problem Solving (CPS) E-Module Development on Ethnoscience-Integrated Thermochemistry Topics - Hastani, Fatmi Sri; Sudarmin, Sudarmin; Pancawardhani, Helina (International Journal of Active Learning, 2021)
Critical thinking and problem-solving skills (CPS) are included in the 21stcentury competencies that are emphasized in K13. However, this ability is still low because there is less emphasis on learning. One of the devices that can be used as a means to train students in both cases is through e-modules. CPS provided through e-modules is more meaningful if it integrates material with ethnoscience. In this study, an e-module has been developed through the R&D method which aims to provide students' CPS skills. The feasibility value of the emodule is 88.26% (material expert) and 92.14 (media expert), while the practicality value is 77.95%. Based on the results of data analysis, it can be concluded that the e-module which developed feasible and practical to use.